2019
DOI: 10.1063/1.5037660
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the concentration and penetration depth of long-lived RONS in plasma-activated water by UV absorption spectroscopy

Abstract: Reactive oxygen and reactive nitrogen species (RONS) are believed to play a key role in biomedical applications, which means that RONS must reach the target tissue to produce a therapeutic effect. Existing methods (electron spin spectrometry and microplate reading) to determine the RONS concentration are not suitable for experimental real-time measurements because they require adding an indicating reagent to the plasma-treated medium, which may alter the chemical composition of the medium. In this paper, we pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 41 publications
2
38
0
Order By: Relevance
“…At the needle-dielectric plate distance of 4 and 5 cm, the voltages are 15 (Figure 10(a)) and 20 (Figure 10(e)) kV, respectively. e UV/Vis spectra of these two images, that is, same contours and peak positions, are similar to those obtained by Oh et al [25] and Liu et al [27]. At the needle-dielectric plate distance of 4 and 3 cm, a voltage of 20 kV (Figures 10(b) and 10(d)), and treatment of 10 min, the UV/Vis spectra are the same as those observed in previous studies.…”
Section: Uv/vis Spectra Of Pawsupporting
confidence: 84%
See 3 more Smart Citations
“…At the needle-dielectric plate distance of 4 and 5 cm, the voltages are 15 (Figure 10(a)) and 20 (Figure 10(e)) kV, respectively. e UV/Vis spectra of these two images, that is, same contours and peak positions, are similar to those obtained by Oh et al [25] and Liu et al [27]. At the needle-dielectric plate distance of 4 and 3 cm, a voltage of 20 kV (Figures 10(b) and 10(d)), and treatment of 10 min, the UV/Vis spectra are the same as those observed in previous studies.…”
Section: Uv/vis Spectra Of Pawsupporting
confidence: 84%
“…( erefore, H 2 O 2 absorption was separated from total absorption. e concentration of H 2 O 2 in the solution could be calculated using the absorbance of PAW at 250 and 255 nm [27].…”
Section: Spectral Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…[ 24–27 ] Plasma‐treated water (PTW) derived from various plasma sources under the different conditions has been well evaluated with respect to generated chemical species, stabilities, and reactivities. [ 28–31 ] Shainsky et al [ 32 ] reported that acidified plasma‐treated water produced by air or oxygen in a closed plasma system exhibited different pH stability and oxidizing properties. Other investigations have reported that two different types of plasma devices fed with air were compared, and it was revealed that the differential reactivities against antimicrobial and organic decomposition were induced due to the differential reactive species composition and its stability, even after post‐treatment storage.…”
Section: Introductionmentioning
confidence: 99%